2018
DOI: 10.1096/fj.201801536r
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid deficiency on FGF pathwayviaBrachyury regulation in neural tube defects

Abstract: Folate deficiency in early development leads to disturbance in multiple processes, including neurogenesis during which fibroblast growth factor (FGF) pathway is one of the crucial pathways. Whether folic acid (FA) directly affects FGF pathways to influence neurodevelopment and the possible mechanism remains unclear. In this study, we presented evidence that in human FA‐insufficient encephalocele, the FGF pathway was interfered. Furthermore, in Brachyury knockout mice devoid of such T‐box transcription factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Furthermore, inadequate folate levels may disrupt the fibroblast growth factor (FGF) pathways. FGF concentrations have been correlated with insulin resistance, and the regulation of visceral adiposity, by FGF stimulates adipokines and inflammatory factors, thereby fostering the progression of lipotoxic liver disease ( 27 , 28 ). Thirdly, folate exerts regulatory control over the transcription of NADPH oxidase, effectively mitigating the oxidative stress induced by a high-fat diet ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inadequate folate levels may disrupt the fibroblast growth factor (FGF) pathways. FGF concentrations have been correlated with insulin resistance, and the regulation of visceral adiposity, by FGF stimulates adipokines and inflammatory factors, thereby fostering the progression of lipotoxic liver disease ( 27 , 28 ). Thirdly, folate exerts regulatory control over the transcription of NADPH oxidase, effectively mitigating the oxidative stress induced by a high-fat diet ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary neurulation is initiated at the neural plate, a condensation of specialized ectodermal cells, and starts around day 19 after fertilization. The plate undergoes fundamental transformations of shape ( Figure 2 ), cell morphology and size, during which the neural plate bends, the prerequisite for forming neural folds ( 32 , 34 ).Furthermore Chang et al demonstrated in Brachyury knock out mice that folic acid deficiency interferes neural induction via inactivation of the FGF pathway ( 35 ).…”
Section: Recapitulation Of Human Organogenesismentioning
confidence: 99%
“…In the subthreshold inoculum model, instead of suppressing tumor growth, chemotherapy promoted tumor growth in small or dormant tumors via tumor-promoting debris [ 1 , 3 ]. Similarly, chemotherapy-generated tumor cell “debris” (apoptotic and necrotic cells and cell fragments) promotes cancer progression and metastasis via stimulating an eicosanoid-driven cytokine storm of pro-inflammatory and pro-angiogenic mediators [ 1 , 2 , 14 , 38 , 39 , 57 , 76 ], polarizing tumor-associated macrophages (TAMs) as well as inducing immunosuppression and limiting anti-tumor immunity [ 24 , 77 , 78 ]. Thus, new approaches to stimulate the clearance of tumor cell debris are urgently needed [ 1 , 21 , 40 , 78 80 ].…”
Section: Chemotherapy-stimulated Cancermentioning
confidence: 99%